In vitro transcription–translation using bacterial genome as a template to reconstitute intracellular profile. Issue 19 (30th August 2017) - Fujiwara, Kei; Sawamura, Tsunehito; Niwa, Tatsuya; Deyama, Tatsuki; Nomura, Shin-ichiro M.; Taguchi, Hideki; Doi, Nobuhide
Abstract: In vitro transcription–translation systems (TX–TL) can synthesize most of individual genes encoded in genomes by using strong promoters and translation initiation sequences. This fact raises a possibility that TX–TL using genome as a template can reconstitute the profile of RNA and proteins in living cells. By using cell extracts and genome prepared from different organisms, here we developed a system for in vitro genome transcription–translation (iGeTT) using bacterial genome and cell extracts, and surveyed de novo synthesis of RNA and proteins. Two-dimensional electrophoresis and nano LC–MS/MS showed that proteins were actually expressed by iGeTT. Quantitation of transcription levels of 50 genes for intracellular homeostasis revealed that the levels of RNA synthesis by iGeTT are highly correlated with those in growth phase cells. Furthermore, activity of iGeTT was influenced by transcription derived from genome structure and gene location in genome. These results suggest that intracellular profiles and characters of genome can be emulated by TX–TL using genome as a template.